Numerical Assessment of Integrated Perforated and Recurved Seawall Designs for Tsunami Mitigation - Weixiao Jiang; Wei Chek Moon; Huanhuan Du; Tze Liang Lau; How Tion Puay; Jin Chai Lee (Civil Engineering Journal, 2026)
Tsunami wave overtopping remains a major challenge for conventional vertical seawalls. Alternative seawall designs have therefore been proposed to address the overtopping issue. This study aims to conduct a staged numerical investigation to evaluate the hydraulic performance of solid, perforated, and integrated perforated–recurved seawall configurations. Tsunami-like waves were simulated in a numerical flume at two impoundment depths under dry and wet bed conditions. The results reveal that perforation significantly reduced peak horizontal wave forces by about 25-30%, depending on the perforation ratio and wave conditions. Nevertheless, this force reduction led to an increase in overtopping discharge, along with higher inland flow depth and velocity. This demonstrates that wave energy is redistributed rather than eliminated. The subsequent multi-criteria performance evaluation found that a 20% perforation ratio offers an optimal compromise between hydraulic performance and material efficiency. Building on this configuration, two types of integrated perforated-recurved seawalls were tested, incorporating triangular and arc-recurved profiles. The results indicate that the addition of the recurved crest elements in the design improved overall energy dissipation from approximately 52% (perforated-only) to over 90% for near-threshold overtopping under dry bed conditions. Among the integrated design types, triangular recurved performed slightly better than arc types. Incorporating perforations and recurves partially offset the disadvantages of each design, and these results demonstrate that such a design is effective and adaptable for mitigating coastal flood risk and improving coastal resilience against tsunamis.